Electrochemotherapy and basal cell carcinomas: First-time appraisal of the efficacy of electrochemotherapy on survivorship using FACE-Q. (March 2021) - Lyons, Phoebe; Kennedy, Alison; Clover, A.James P.
Summary: Introduction: The establishment and success of new treatments are significantly influenced by patient satisfaction. Post-operative scarring is an important outcome for patients, and subsequently influences overall satisfaction with treatment. The objective was to measure post-treatment scarring satisfaction using a novel scale, the FACE-Q Skin Cancer Module, to compare electrochemotherapy (ECT) to traditional surgical excision (SE) to demonstrate equivalence of ECT and SE regarding outcome and survivorship. Methods and materials: This was a multicentre first-time appraisal study of the efficacy of ECT. All patients with facial BCCs treated with either ECT or SE were deemed eligible and subsequently recruited from either a previous clinical trial or outpatient clinics, respectively. Of the 40 participants invited, 25 responses were received. Patient information recorded included age, gender, location and size of BCCs, and time since treatment. Patient outcomes were measured using the FACE-Q Skin Cancer Module. Results: The ECT and SE groups consisted of 14 and 11 patients, respectively. Mean age was 68 years (M: F  = 16:9), while mean time since treatment was 4.98 years (range 0.3–9.58 years). Appraisal of scars was significantly higher in the ECT cohort versus SE ( p  = 0.034). Cancer worry was equivalent across both cohorts ( p  = 0.804). According to treatment type, no correlation was detected between time since treatment and both appraisal of scars (ECT p  = 0.466 and SE p  = 0.214) and adverse effects (ECT p  = 0.924 and SE p  = 0.139). Conclusion: Based on this study, ECT has superior scar outcomes and overall equivalence to SE. This demonstrates high patient satisfaction for those treated with ECT without any additional cancer worry.